2016
DOI: 10.3389/fpsyg.2016.01599
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Information Processing and its Relation to Executive Functions in Elderly Individuals

Abstract: Normal aging triggers deterioration in cognitive functions. Evidence has shown that these age-related changes concern also executive functions (EF) as well as temporal information processing (TIP) in a millisecond range. A considerable amount of literature data has indicated that each of these two functions sets a frame for our mental activity and may be considered in terms of embodied cognition due to advanced age. The present study addresses the question whether in elderly subjects the efficiency of TIP is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…In our previous report we extended the relation “ timing-cognition ,” indicating correlations between the efficiency of temporal resolution and executive functions (Nowak et al, 2016 ). It suggests a common neural mechanisms underlying these two mental functions.…”
supporting
confidence: 57%
“…In our previous report we extended the relation “ timing-cognition ,” indicating correlations between the efficiency of temporal resolution and executive functions (Nowak et al, 2016 ). It suggests a common neural mechanisms underlying these two mental functions.…”
supporting
confidence: 57%
“…As mentioned in ''Introduction'' section, previous studies have suggested that TIP plays an important role in numerous cognitive functions, such as language, attention, learning, executive processes, and WM (Pöppel, 1997;Poeppel, 2003;Szymaszek et al, 2009;Ulbrich et al, 2009;Nowak et al, 2016). Because of the specific temporal dynamics of these functions, it can be assumed that they are rooted in a defined time template creating the neural frame for our mental activity.…”
Section: The "Wm-tip" Relationshipmentioning
confidence: 99%
“…One may assume, therefore, that TIP constitutes a neural basis for mental activity in both normal and pathological conditions, including cognitive declines in healthy aging (e.g., Szymaszek et al, 2009;Teixeira et al, 2013). Accumulated data have also indicated age-related deterioration in TIP (e.g., Fitzgibbons and Gordon-Salant, 1994;Kolodziejczyk and Szelag, 2008;Szymaszek et al, 2009;Kumar and Sangamanatha, 2011;Nowak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations